Визнання юридичної особи суб'єктом кримінальної відповідальності: про блеми сьогодення - Дорохіна, Юлія Анатоліївна; Дорохина, Юлия Анатольевна; Dorohina, Julija (Одеса : Юрид. л-ра, 2012)
The question of recognition of the legal entity as the subject of criminal charges in the Ukrainian and international legislation. Contradictory illumination is analysed in scientific domestic and foreign literature, and also in different approaches of legislators of different countries of regulation of criminal responsibility of legal entities. It is noticed that all reasons of authors in relation to pointlessness of criminal responsibility of legal entities of непереконливі and does not lean against sufficient empiric, legislative bases, and also detailed researches of predecessors.
Дорохіна Ю. А. Визнання юридичної особи суб'єктом кримінальної відповідальності: проблеми сьогодення / Ю. А. Дорохіна // Актуальні проблеми держави і права : зб. наук. пр. /редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю .П. Аленін [та ін.] ;МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 67. - С. 584-591.
Keywords: юридична особа; суб'єкт; кримінальна відповідальність; юридическое лицо; субъект; уголовная ответственность; juridical person; subject; criminal liability